2004
DOI: 10.1002/ajmg.b.30090
|View full text |Cite
|
Sign up to set email alerts
|

Mutation screen of the brain derived neurotrophic factor gene (BDNF): Identification of several genetic variants and association studies in patients with obesity, eating disorders, and attention‐deficit/hyperactivity disorder

Abstract: Several lines of evidence indicate an involvement of brain derived neurotrophic factor (BDNF) in body weight regulation and activity: heterozygous Bdnf knockout mice (Bdnf(+/-)) are hyperphagic, obese, and hyperactive; furthermore, central infusion of BDNF leads to severe, dose-dependent appetite suppression and weight loss in rats. We searched for the role of BDNF variants in obesity, eating disorders, and attention-deficit/hyperactivity disorder (ADHD). A mutation screen (SSCP and DHPLC) of the translated re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
91
1
6

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(103 citation statements)
references
References 32 publications
(30 reference statements)
5
91
1
6
Order By: Relevance
“…This finding partially replicates a recent report showing that girls who were Met carriers had a tendency for higher BMI (Akkermann et al, 2011), however in contrast to our participants, these Caucasian girls of Estonian origin practiced extreme weight restriction behaviors. On the other hand, our results diverge from a study of young participants of German origin that failed to detect significant differences in the distribution of the BDNF Val66Met variants between extremely obese children and adolescents, underweight students, patients with attention deficit hyperactivity disorder, anorexia nervosa, bulimia nervosa and normal weight controls (Friedel et al, 2005), and from the data showing no association between BDNF Val66Met and susceptibility to develop eating disorders in Spanish schoolchildren of Caucasian background (Arija et al, 2010). The discrepancies between our and the aforementioned results might be explained by the fact that we included only healthy young participants, while other studies (Akkermann et al, 2011;Arija et al, 2010;Friedel et al, 2005) included either extremely obese or underweight participants, as well as subjects with eating disorders or risk for eating disorders.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…This finding partially replicates a recent report showing that girls who were Met carriers had a tendency for higher BMI (Akkermann et al, 2011), however in contrast to our participants, these Caucasian girls of Estonian origin practiced extreme weight restriction behaviors. On the other hand, our results diverge from a study of young participants of German origin that failed to detect significant differences in the distribution of the BDNF Val66Met variants between extremely obese children and adolescents, underweight students, patients with attention deficit hyperactivity disorder, anorexia nervosa, bulimia nervosa and normal weight controls (Friedel et al, 2005), and from the data showing no association between BDNF Val66Met and susceptibility to develop eating disorders in Spanish schoolchildren of Caucasian background (Arija et al, 2010). The discrepancies between our and the aforementioned results might be explained by the fact that we included only healthy young participants, while other studies (Akkermann et al, 2011;Arija et al, 2010;Friedel et al, 2005) included either extremely obese or underweight participants, as well as subjects with eating disorders or risk for eating disorders.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies examining the possible association between the BDNF Val66Met variants and obesity in healthy children and adolescents are still rare, and one genome wide association study (GWAS) reported significant association between BDNF gene and BMI in healthy children (Zhao et al, 2009), while other studies failed to find any significant association between BDNF Val66Met and obesity (Arija et al, 2010;Friedel et al, 2005). Most of the studies evaluated the role of BDNF Val66Met in eating disorders, and found either a significant association (Akkermann et al, 2011;Gratacos et al, 2007), or no association (Arija et al, 2010;Friedel et al, 2005) between the Met allele and eating disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to having physiological functions, BDNF has recently been associated with neurological diseases. For example, Val66Met functional polymorphism in human BDNF is involved in the pathogenesis of attentiondeficit hyperactivity disorder (ADHD) (Egan et al 2003;Friedel et al 2005;Kent et al 2005). Interestingly, a pericentric inversion breakpoint in the DOCK3 gene has been described in ADHD patients (de Silva et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The second study failed to find any association between Val66Met and childhood ADHD using a small sample (N ¼ 88), but this study's power to detect an association with an effect size of 1.6, at an alpha of 0.05 was only 45%. 31 It is also important to consider that different diagnostic practices between the UK, other parts of Europe and the US may be an issue with regards to the failure to replicate findings, particularly in terms of the differing frequencies of ADHD subtypes and comorbidity seen in other samples.…”
Section: Discussionmentioning
confidence: 99%